Development of a covalent cereblon-based PROTAC employing a fluorosulfate warhead - Nowak, Rados aw P; Ragosta, Leah; Huerta, Fidel; Liu, Hu; Ficarro, Scott B; Cruite, Justin T; Metivier, Rebecca J; Donovan, Katherine A; Marto, Jarrod A; Fischer, Eric S; Zerfas, Breanna L; Jones, Lyn H (RSC chemical biology, 2023)
Many cereblon (CRBN) ligands have been used to develop proteolysis targeting chimeras (PROTACs), but all are reversible binders of the E3 ubiquitin ligase. We recently described the use of sulfonyl exchange chemistry to design binders that covalently engage histidine 353 in CRBN for the first time. Here we show that covalent CRBN ligands can be used to develop efficient PROTAC degraders. We demonstrate that the fluorosulfate PROTAC FS-ARV-825 covalently labels CRBN in vitro , and in cells the BRD4 degrader is insensitive to wash-out and competition by potent reversible CRBN ligands, reflecting enhanced pharmacodynamics. We anticipate that covalent CRBN-based PROTACs will enhance degradation efficiencies, thus expanding the scope of addressable targets using the heterobifunctional degrader modality. The first covalent cereblon-based PROTAC was developed using a fluorosulfate warhead to site-specifically engage His353 in the sensor loop of the E3 ligase, yielding a degrader with prolonged pharmacodynamics.